Rethinking The Roles and Institutions of Pawang Uteun for Sustainable Forest Management: Literature Review - Dian Aswita; Suleman Samuda; Evi Apriana; Herlina Herlina (Universitas Serambi Mekkah, 2022)
Customs that are sourced from local traditions and knowledge offer alternative perspectives for solutions in environmental management, one of which is sustainable forest governance. Local knowledge contains about how to interact and use resources born of an adaptive process with nature and the environment which is transmitted orally and shared practice from generation to generation. This study discusses the role of the pawang uteun in using their cultural authority as a manifestation of Traditional Ecological Knowledge to respond to the increasingly complex forest governance in Aceh. This research is a literature review research, using library research method. Data obtained from several articles and books, which were analyzed using descriptive analysis techniques. From the results of the study, it is known that studies related to Pawang Uteun discuss more about the role of institutions, customary law and as Indatu Tradition but very minimally discuss the existence of Pawang Uteun from the perspective of local ecological knowledge and the ecological wisdom of Acehnese indigenous peoples as a solution in overcoming forest destruction. The Pawang Uteun is only seen as a traditional representation but ignores the Pawang Uteun as a manifestation of local knowledge about ecological wisdom. The diminishing role of the pawang utuen (delegation) is directly proportional to the high rate of clearing of forest land cover. Keywords: pawang uteun, ecological wisdom, local knowledge, sustainability.